IMPLEMENTASI KOORDINASI ANTARA UNIT KOBOK (BANDAR UDARA MARIMOI) DENGAN UNIT TERNATE APP (COMBINE TWR) DALAM PELAYANAN LALU LINTAS UDARA - Choirunnas Rizky Alexandrianto; Dewi Ratnasari; Putu Agus Valguna (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Sultan Babullah Airport is a Class III airport located in Ternate, North Maluku. This airport provides air traffic services for military aircraft and commercial aircraft. With the increasing number of aircraft traffic, ATC must provide a safe, orderly and efficient service. However, the reality is that from the KOBOK side there was no coordination in the release of the aircraft, resulting in a breakdown of separation between the departure Kobok aircraft and other aircraft. Referring to "CASR part 170 Air Traffic Rules subpart 170.018 on Coordination of activities potentially hazardous to civil aircraft" which means the purpose of coordination is to create good arrangements to avoid hazards and minimize interference with normal flights. The author hopes that this paper can be used as a consideration for Perum LPPNPI, Ternate Sub-Branch Office and from the Kobok concerned so that they can coordinate and disseminate information regarding request clearance. In the end, it is hoped that with the socialization of the importance of coordinating the traffic departure from Kobok with other aircraft, they will separate so as to create in-flight safety.